Assessment of Healthcare Solid Waste Composition, Generation and its Management: the case of Two Hospitals of Shashemene Town, Oromia Regional State, Ethiopia - Gudeta Elie; Daniel Fitamo; Semere Gebreaegawi (East African Journal of Biophysical and Computational Sciences)
Hazardous wastes from Hospitals could pose a threat to the health of healthcare workers, the general public, and the environment unless managed properly. The study aimed to appraise the healthcare waste (HCW) composition, generation rate and the prevailing management practices in two Hospitals (a Private and a Government-owned) of Shashemene Town, Ethiopia. A cross-sectional study involving Direct Observation, Key Informant Interview, Questionnaire survey and Weighting Scale was conducted to evaluate the current HCW management practices and to quantify the HCW generation rate. Data was analyzed using SPSS version 20. The mean generation rates of HCW were 45.2 ± 5.8kg day–1 (0.20kgbed‒1day‒1) and 20 ± 2.4 kg day–1 (0.19kg bed‒1day‒1) from Government Hospital(GH) and Private Hospital (PH), respectively. Of the total solid waste generated, over half(GH: 53.3%; PH: 57.1%) constituted general waste (GW), and the remaining (GH: 46.7%; PH: 42.9%) comprised hazardous waste (HW), which exceeded the WHO threshold(10‒25%) intimates the lack of poor waste segregation. There were significant variations between the hospital wards regarding GW (GH: χ2 = 31; P < 0.001; PH:χ2 = 13; P <0.01), HW (GH: χ2 = 25; P < 0.001; PH: χ2 = 10; P < 0.01), and total HCW (GH: χ2 = 46; P < 0.01; PH: χ2 = 22; P < 0.01). Besides, significant differences were observed between the mean total HCW (χ2 = 9.016; P < 0.01), GW (χ2 = 9.8; P < 0.01), and the HW (χ2 =5.011, P < 0.05) of the hospitals. Segregation of wastes and pre-treatment of infectious wastes were not properly practiced, and single-chamber incinerators was the most utilized treatment method indicating poor management of the HCW. The study establishes that the little attention is given to medical waste management which primarily proceeds from a lack of due implementation of the national healthcare wastes management guideline/directive at the healthcare facility level. If the poor healthcare solid waste management is not properly addressed at the study hospitals, human (healthcare workers, waste handlers, patients, and nearby community) and environmental health risk will be within the bounds of possibility.